2017
DOI: 10.1042/cs20170049
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic nervous activity in patients with acute coronary syndrome: a comparative study of inflammatory biomarkers

Abstract: Previous studies have shown that both sympathetic hyperactivity and enhanced inflammatory responses are associated with poor outcomes in patients with acute coronary syndrome (ACS). Whether there is a correlation between these two characteristics remains unclear. Thirty-four patients with uncomplicated ACS were evaluated; their mean age was 51.7±7.0 years, 79.4% were male, and 94.1% had myocardial infarction (MI). On the fourth day of hospitalization, they underwent muscle sympathetic nerve activity (MSNA) ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…SARS-CoV-2 infection is also associated with inflammatory cytokine storms, which can have sweeping implications to the respiratory system, vasculature, and nervous system (Paybast et al, 2020). While inflammatory cytokine storms can be life-threatening, even relatively mild increases in inflammatory biomarkers result in oxidative stress (Tank et al, 2011;Moreira et al, 2017). These proinflammatory mediators can subsequently cross the blood brain barrier, ultimately increasing activation of the sympathetic nervous system (SNS) (Pongratz & Straub, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SARS-CoV-2 infection is also associated with inflammatory cytokine storms, which can have sweeping implications to the respiratory system, vasculature, and nervous system (Paybast et al, 2020). While inflammatory cytokine storms can be life-threatening, even relatively mild increases in inflammatory biomarkers result in oxidative stress (Tank et al, 2011;Moreira et al, 2017). These proinflammatory mediators can subsequently cross the blood brain barrier, ultimately increasing activation of the sympathetic nervous system (SNS) (Pongratz & Straub, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Increases in resting and reactive sympathetic activity can have detrimental effects on several physiological systems, including alterations in cardiac contraction (Moreira et al . 2017), impairments in vascular function (Thijssen et al . 2006) and reductions in exercising blood flow capacity (Stuckless & Pyke, 2015); accordingly, sympathetic overdrive has been identified as an independent predictor of mortality in a number of diseases (Grassi et al .…”
Section: Introductionmentioning
confidence: 99%
“…In the ischemic area, oxidative stress builds up, and myocardial cell’s ability to produce vasodilator substances decreases. Mechanically, some injured cardiomyocytes leading to a decrease in myocardial contractility, which is compensated by an increase in sympathetic activity and the secretion of catecholamines as well as angiotensinogen, which aims to maintain peripheral hemostasis function [ 1 – 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Second, studies have indicated that a shorter lifespan is associated with elevated heart rate (Zhang & Zhang, 2009). An increased heart rate could cause a subsequent elevation of reactive oxygen species (Luo et al, 2020), inflammatory cytokines, glucose-lipid metabolism disturbance (Saladini & Palatini, 2018), and abnormal activation of the immune system (Moreira et al, 2017). These physiological dysfunctions could easily contribute to the impairment of organ function and lead to an adverse outcome, including death.…”
Section: Discussionmentioning
confidence: 99%